Dementia after DBS Surgery: A Case Report and Literature Review. (29th November 2011) - Rektorova, I.; Hummelova, Z.; Balaz, M.
Abstract : We report the case history of a 75-year-old woman with Parkinson's disease who developed severe cognitive problems after deep brain stimulation (DBS) of the bilateral subthalamic nuclei (STN). After a brief cognitive improvement, the patient gradually deteriorated until she developed full-blown dementia. We discuss the case with respect to the cognitive effects of STN DBS and the possible risk factors of dementia after STN DBS surgery.